Psychometric properties of the TMMS-24 emotional intelligence scale in Peruvian university students - Fernández-Berrocal, Pablo; Vilca-Pareja, Vilma; Rojas Zegarra, Maria Elena; Hillpa-Zuñiga, Manuel Edmundo; Yana-Calla, Victor Ritchar; Cabello, Rosario (Frontiers in Psychology, 2025)
IntroductionThis study investigates the psychometric properties of the Spanish-adapted version of the Trait Meta-Mood Scale (TMMS-24) in Peruvian university students. University life presents significant challenges that can negatively impact students’ mental health, increasing the prevalence of anxiety and depression. Emotional intelligence (EI) has been identified as a crucial protective factor in this context. The TMMS-24 is a widely used self-report instrument that assesses individuals’ perceptions of their own EI, encompassing three dimensions: emotional attention, emotional clarity, and emotional regulation.MethodThis study analyzed the psychometric properties pertaining to TMMS-24, such as the reliability and validity of this instrument on Peruvian Students. The analysis was made on 1315 students whose ages ranged from 18 to 30 years of age (M = 20.03, SD = 2.24).ResultsThe findings confirmed high reliability and internal consistency, with Cronbach’s alpha coefficients exceeding 0.80 for all three subscales. Test-retest reliability, a novel finding in the Peruvian context, was significant, indicating good temporal stability. Confirmatory Factor Analysis supported the original three-dimensional structure (Attention, Clarity, and Repair). Construct validity was evidenced by factor loadings ranging from 0.32 to 0.85, which is consistent with previous research. Regarding gender differences, males reported significantly higher scores in emotional clarity and repair, while no significant differences were found in emotional attention. A positive correlation between cognitive reappraisal and EI and a negative correlation between suppression and EI supported convergent and discriminant validity. Furthermore, significant positive correlations were observed between all TMMS-24 dimensions and personality traits (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness). These results provide evidence for the reliability and validity of the TMMS-24 for assessing perceived EI in Peruvian university students.DiscussionThese findings have significant implications for researchers and educational interventions in Peru and their impact on mental health and academic success in this population.